The idea of cultivation in the philosophy of al-Ghazali (Eurasian Journal of Religious Studies, 2018)
The problem of achieving a certain perfection in the Eastern medieval Arabic philosophy and theology takes one of the central places. The search for an adequate solution to the problem of spiritual and moral improvement in the philosophy of al-Ghazali is associated with the search for ways of a certain perfection. And thanks to the profound philosophical and theological studies of the thinkers of the past, ideas were expressed, which today are gratefully perceived by modernity. Most thinkers of the East noted in their treatises the natural desire of man to happiness, and happiness is understood for example alFarabi as a certain degree of perfection, as a kind of perfect goal. The same idea distinguishes al-Ghazali. He understands human perfection as the achievement of the quality of an angel. In this case, a person is awarded obedience to God. This kind of honoring is, according to al-Ghazali, a certain degree of human perfection. However, perfection does not come by itself. Al-Ghazali believes that perfection is understood as the mastery of knowledge and the combination of it with deeds and actions. He is aware of the need for what knowledge and the ways that lead to perfection as goals are. The search for perfection must begin with the knowledge of the essence of man. It is possible to achieve the degree of perfection only by going through the inner struggle. In order to achieve a certain degree of perfection a person has to go through a difficult path during his life.